Evaluation of vertical ground reaction force during walking in patients with multiple sclerosis - Mostafa Payandeh; Rahman Amiri Jomi Lo; Shahnaz Bakhshi Nezhad; Khaled Takizadeh (Gonabad University of Medical Sciences, 2017)
Patients with Multiple Sclerosis (MS) suffer from inabilities such as weakness and muscle fatigue due to the demyelination. The inabilities may result in some disorders in walking. The present study is a clinical trial research conducted on 84 participants in two groups of experimental and control who were randomly selected. The results showed that people with MS apply more force on the ground during the three examined component of stance phase of gait cycle in comparison with those without the disease. Also, the maximum difference was found between the two groups at the mid-stance component that was the only stage in the stance phase in which, the difference between the groups was statistically significant. It can be concluded that the largest amount of pressure and force applied on the limbs of people with MS lies in the mid-stance component of stance phase. According to the results of the study, the lowest amount of force absorption occurs in that stage. The obtained results can be employed in order to design shoes of type suitable for people with MS that are capable to absorb extra vertical reaction force and thus, prevent skeletal-muscle damages.